تأثير نوع السياسة التمريضيَّة على الوقاية من اختلاطات الديال الدموي: دراسة مقارنة - غزال, سوسن; سليمان, إبراهيم; سليمان, مجد (Latakia University Journal -Medical Sciences Series, 2016)
المقدّمة: قد لوحظ أن تطبيق سياسة رعاية تمريضيَّة متكاملة متضمنة برنامج تمارين رياضية لها دور في تحسين فعالية الديال الدموي وفي الوقاية من حدوث كثير من الاختلاطات خلال جلسة الديال الدموي. الهدف: أجري البحث لدراسة تأثير نوع السياسة التمريضية على الوقاية من اختلاطات الديال الدموي (دراسة مقارنة).مواد البحث وطرائقه: أجري البحث على عينة قوامها 45 مريضاً ومريضة في قسم الكلية الصناعية في مشفى الأسد الجامعي في اللاذقية، وتم تطبيق سياستي رعاية تمريضية، حيث طبقت كل سياسة على المجموعتين التجريبيتين الأولى والثانية لمدة 3 أشهر، وتمت مراقبة المرضى باستخدام استمارة مؤلفة من 3 أجزاء وهي البيانات الديموغرافية وأنشطة الرعاية التمريضية ومراقبة حدوث الاختلاطات. النتائج: أوضحت نتائج الدراسة فعالية تطبيق سياسة رعاية تمريضية متضمنة برنامج تمارين رياضية في الوقاية من حدوث الاختلاطات خلال الديال الدموي، إذ أظهرت الدراسة دور التمارين الرياضية في الوقاية من الاختلاطات وفعاليتها خلال الديال الدموي بغض النظر عن أنشطة البرنامج الرياضي المطبق. الاستنتاجات: نستنتج من الدراسة أن تطبيق سياسة رعاية تمريضية متضمنة برنامج تمارين رياضية يساهم في الوقاية من حدوث الاختلاطات (ارتفاع/انخفاض ضغط الدم، والغثيان والإقياء، وتشنج العضلات) خلال جلسة الديال الدموي. Introduction: It has been observed that the application of the policy of nursing care, including integrated exercise program have a role in improving the effectiveness of hemodialysis in the prevention of the occurrence of a lot of complications during hemodialysis session. Objective: The research was conducted to study the effect of the type of nursing policy on the prevention of complications of hemodialysis (comparative study). Research Material and Methods: Research was conducted on a sample of 45 patients in the Department of hemodialysis in Alssad University Hospital in Latakia, It was implemented two policies nursing care included each policy applied on two experimental groups I and II for a period of 3 months, and the patients were monitored patients using the form author 3 parts of a demographic data and the activities of nursing care and monitoring the occurrence of complications. Results: The results showed the effectiveness of the application of the policy of nursing care, including exercise program in the prevention of the occurrence of complications during hemodialysis, effectiveness of exercise in the prevention of complications during hemodialysis, regardless of the activities of the sports program applied. Conclusions: conclude from the study that the application of the policy of nursing care, including exercise program contributes to the prevention of the occurrence of complications (high / low blood pressure, nausea and vomiting, muscle spasm) during a session of hemodialysis.